2013
DOI: 10.2147/ndt.s32302
|View full text |Cite
|
Sign up to set email alerts
|

Review: management of Parkinson's disease

Abstract: Parkinson’s disease (PD) is one of the most frequent neurological diseases. Despite the modern imaging and nuclear techniques which help to diagnose it in a very early stage and lead to a better discrimination of similar diseases, PD has remained a clinical diagnosis. The increasing number of available treatment options makes the disease management often complicated even when the presence of PD seems undoubted. In addition, nonmotor symptoms and side effects of some therapies constitute some pitfalls already i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 172 publications
(140 reference statements)
1
43
0
1
Order By: Relevance
“…In 2011, a review suggested that piribedil, pramipexole, rotigotine, ropinirole, pramipexole extended release, pergolide, and cabergoline were efficacious as symptomatic monotherapies for motor symptoms of PD, and ropinirole prolonged release was likely efficacious [18]. There was also a study that summarized medical treatments for the most common motor and non-motor symptoms in PD [19]. In the current study, a network meta-analysis method is used for the quantitative comparison of different drug therapies for the treatment and management of PD to determine the optimal treatment and course of management for PD [20].…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, a review suggested that piribedil, pramipexole, rotigotine, ropinirole, pramipexole extended release, pergolide, and cabergoline were efficacious as symptomatic monotherapies for motor symptoms of PD, and ropinirole prolonged release was likely efficacious [18]. There was also a study that summarized medical treatments for the most common motor and non-motor symptoms in PD [19]. In the current study, a network meta-analysis method is used for the quantitative comparison of different drug therapies for the treatment and management of PD to determine the optimal treatment and course of management for PD [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several drugs (e.g. levodopa) have been developed for the treatment of PD, but there are none that can alter the underlying neurodegenerative process [2,3]. Recently, the concept of ''neuroprotective therapy'' has emerged as a potential treatment for PD [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…While STN and GPi are the main targets of DBS in PD patients as they alleviate a broader spectrum of motor symptoms, in contrast to Vim which helps primarily with tremors [1], the benefit of their stimulation on axial and nonmotor symptoms is limited [2]. D. Anderson et al describe the role of emerging alternative DBS targets such as the pedunculopontine nucleus, caudal zona incerta, substantia nigra pars reticulata, and the motor cortex for control of axial symptoms such as freezing, postural instability, gait, speech, and swallowing and nonmotor symptoms such as memory impairment, attention decline, and sleep disturbances in PD patients.…”
mentioning
confidence: 99%